2015
DOI: 10.1080/02626667.2013.875177
|View full text |Cite
|
Sign up to set email alerts
|

Bivariate index-flood model: case study in Québec, Canada

Abstract: 21Floods, as extreme hydrological phenomena, can be described by more than one 22 correlated characteristic such as peak, volume and duration. These characteristics should 23 be jointly considered since they are generally not independent. For an ungauged site, 24 univariate regional flood frequency analysis (FA) provides a limited assessment of flood 25 events. A recent study proposed a procedure for regional FA in a multivariate framework. 26This procedure represents a multivariate version of the index-flood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…These allow for separate studies of the marginal distributions of the component variables and the correlation/dependence structure between them. Numerous studies have been published on this topic (e.g., Shiau, 2003;De Michele et al, 2005;Chowdhary et al, 2011;Requena et al, 2013), including recommendations how to select appropriate copula models (e.g., Favre et al, 2004;Genest and Favre, 2007). Despite numerous studies, as mentioned by Chowdhary et al (2011), the use of copula-based multivariate distributions for hydrological design still cannot be regarded as having been satisfactorily resolved.…”
Section: Introductionmentioning
confidence: 99%
“…These allow for separate studies of the marginal distributions of the component variables and the correlation/dependence structure between them. Numerous studies have been published on this topic (e.g., Shiau, 2003;De Michele et al, 2005;Chowdhary et al, 2011;Requena et al, 2013), including recommendations how to select appropriate copula models (e.g., Favre et al, 2004;Genest and Favre, 2007). Despite numerous studies, as mentioned by Chowdhary et al (2011), the use of copula-based multivariate distributions for hydrological design still cannot be regarded as having been satisfactorily resolved.…”
Section: Introductionmentioning
confidence: 99%
“…may not be overcome in the scope of such a regional comparative analysis even in the case of using all available independent flood events differentiated by processes. Based on this comparative study and results of other more advanced studies (e.g., Serinaldi, 2013Serinaldi, , 2015 it can be concluded that if reliable predictions are required for an important engineering application, the benefits of regional bivariate frequency analysis methods could be further explored (e.g., Ben Aissia et al, 2015) or the potential of the combination of rainfall generators, rainfall-runoff models, analysis of historical floods and advanced statistics considering uncertainty might be utilized as, e.g., in Grimaldi et al (2016).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, RFA involves two main steps: (1) the formation and identification of homogeneous regions and (2) the estimation of extreme events. Attention has been given to index-flood based multivariate RFA recently mainly in the work of Ouarda (2007, 2009), ), Ben Aissia et al (2015, Abdi et al (2016), Requena et al (2016) and Masselot * Correspondence: T. Šimková, Studentská 14022, Liberec 1, 46117, Czech Republic. E-mail: tereza.simkova@tul.cz et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Simulation was also carried out to evaluate the 12 T. Šimková performance of the multivariate index-flood model ). The bivariate RFA based upon the index-flood model was first applied using real data by Ben Aissia et al (2015). Requena et al (2016) have recently presented a comprehensive stepwise procedure for multivariate index-flood model application whilst focusing on a bivariate case study situated in Spain.…”
Section: Introductionmentioning
confidence: 99%